2023
DOI: 10.14744/anatoljcardiol.2022.2003
|View full text |Cite
|
Sign up to set email alerts
|

Histopathological Changes in the Myocardium Caused by Energy Drinks and Alcohol in the Mid-term and Their Effects on Skeletal Muscle Following Ischemia-reperfusion in a Rat Model

Abstract: Background: Although energy drinks have been consumed for many years, their effects on the cardiovascular system continue to be investigated. Today, the most frequently used area of energy drinks is the entertainment sector, and this study investigates the effects of energy drinks and alcohol consumption on rats’ limb and myocardium tissue. Methods: Forty Wistar Albino rats were used and divided into 4 groups. Energy drinks were given to the first group (the energy drin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…These findings suggest that the interaction between flunitrazepam and caffeine can have detrimental effects on cognitive performance. A similar study [18] on energy drinks and alcohol consumption also found that the combination of these two substances can lead to severe damage in heart and muscle tissues. They further explained that this damage can affect gas exchange, result in hypertriglyceridemia, and impact glycemia.…”
Section: Discussionmentioning
confidence: 71%
“…These findings suggest that the interaction between flunitrazepam and caffeine can have detrimental effects on cognitive performance. A similar study [18] on energy drinks and alcohol consumption also found that the combination of these two substances can lead to severe damage in heart and muscle tissues. They further explained that this damage can affect gas exchange, result in hypertriglyceridemia, and impact glycemia.…”
Section: Discussionmentioning
confidence: 71%
“…The hearts of animals perfused with caffeine and taurine showed shortened repolarisation times and refractory periods on the ECG trace, followed by ventricular arrhythmias, confirming the potential arrhythmogenic effect of these substances. In another study, Demirel et al [ 130 ] investigated the effects of the combined consumption of energy drinks and alcohol on the myocardium and skeletal muscle system. In particular, the study highlighted damage to the cardiac and endothelial cytoarchitecture, as well as an increased tendency towards anaerobic cellular respiration in skeletal muscle tissue, resulting in increased lactate formation.…”
Section: Discussionmentioning
confidence: 99%
“…The combination of alcohol with energy drinks has a very adverse effect on the cardiovascular system. From available studies, it is evident that alcohol alone increases the risk of atrial fibrillation [56], but when combined with an energy drink, the effect is compounded, significantly increasing not only the risk of atrial fibrillation [57], but also the risk of other cardiac rhythm disorders and myocardial damage [58][59][60][61][62].…”
Section: State Of Knowledgementioning
confidence: 99%